EFFECT OF TEACHER'S PROFESSIONALISM AND PERSONALITY ON THE ACHIEVEMENT OF MASS AL-WASHLIYAH UNIVA MEDAN STUDENTS - Hotni Sari Harahap; Muhyani Muhyani; Akhmad Alim (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2019)
The purpose of this study is to determine (1) the effect of professionalism competence variable on students' achievement, (2) the effect of teacher's personality variables on students' achievement, (3) the effect of teacher's professionalism and personality on students' achievement. This research is a quantitative descriptive research, with 60 teachers of MAS/SMA al-Washliyah UNIVA as research subjects taken by total sampling method. Data collected by the instrument in form of questionnaire. The data analysis technique used is descriptive analysis method, normality test, multicollinearity test, heteroscedasticity test, hypothesis testing by F test and t test. Results from the study shows regression equation Y = 43.764+ 0,243 X1 + 0.173 X2 that has meaning when variables X1 and X2 changes, it will have an impact on student achievement. The result of data analysis shows that partially teacher's professionalism affects significantly on students' achievement with the value tcount 3,485 > ttable 2,002.Analysis on effect of personality on students' learning achievement partially influences significantly with value tcount 3,105 > ttable 2,002. The result simultaneously shows that teacher's professionalism and personality conjunctly affecting the achievement of MAS/SMA al-Washliyah UNIVA Medan student with value of 8,143 > Ftable 4.01. Other than that, the coefficient of determination (R2) has value of 222. It means in the amount of 22,20% of students' learning achievement variable is affected by two independent variables in this research, meanwhile the rest as big as 77,80% is affected by other variable that is not studied in this research.